Longitudinal Associations of Stressful Life Events with Non-suicidal Self-Injury among Chinese Adolescents: The Mediating Effect of Depressive Symptoms - Wan, Li-Peng; Yang, Xiao-Fan; Liu, Zhen-Zhen; Liu, Bao-Peng; Zhang, Ying-Ying; Liu, Cai-Rui; Liu, Xianchen; Jia, Cun-Xian; Wang, Xin-Ting (Depression and Anxiety, 2023)
Objective. Little is known about the mechanism between stressful life events and non-suicidal self-injury (NSSI) in Chinese adolescents. This study was to investigate the mediating effect of depressive symptoms on the association between stressful life events and NSSI among Chinese adolescents. Methods. This study included a total of 7072 adolescents who participated in the one-year follow-up of Shandong Adolescent Behavior and Health Cohort. A self-administrated questionnaire was used to evaluate stressful life events, depressive symptoms, NSSI, and other variables in November-December 2015. One year later, a follow-up investigation was performed to evaluate participants’ depressive symptoms and NSSI. Logistic regression and mediation analysis were used to examine the relationship between stressful life events, depressive symptoms, and NSSI. Results. Of the sample, half were females and mean age was 14.58±1.46. At baseline and one-year follow-up, the rate of NSSI was 19.4% and 8.8%, respectively. Multivariate logistic regression analysis showed that stressful life events and depressive symptoms were positively associated with NSSI. Mediation analysis showed that depressive symptoms accounted for 17.70% of the relation between high stressful life events and NSSI at one-year follow-up after controlling for covariates. Limitation. All variables were collected based on self-report. Conclusions. The relationship between stressful life events and NSSI appears to be partially mediated by depressive symptoms. It is necessary to evaluate and intervene against depressive symptoms related to life stress for the prevention of NSSI.